Pelatihan Pembuatan Paket Wisata Incentive Travel untuk Mendukung Pariwisata Berkelanjutan di Pulau Harapan - Yosi Erfinda; Nurina Azzyati; I Made Adhi Gunadi; Sabrina Azzahra; Farah Nuhaliza; Indra Setiawan; Nabil Falah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Harapan Island, located in the Thousand Islands National Park, has great potential to be developed as a conservation-based ecotourism and incentive travel destination. However, the management of planned tour packages is still limited. Community service activities were carried out in October–November 2025 to improve the ability of local communities to develop sustainable incentive travel tour packages. The method used was experiential learning through training and mentoring for 25 participants consisting of members of POKDARWIS, homestay owners, MSME actors, and local communities. The training was held on 21 November 2025 in the Multipurpose Room of the Pulau Harapan Village Office. The material covered the concepts of incentive travel, the principles of sustainable tourism, the role of the local community, and basic English communication for tourism. Evaluation through pre-tests and post-tests showed an increase in participants' understanding from 55% to 100%. This activity helped the community develop tourism products that support conservation, sustainability, and local economic improvement, so that Pulau Harapan has the potential to become a leading incentive travel destination.